Destination attributes and tourist’s satisfaction in a cultural destination - Vareiro, Laurentina (2017)
Cultural tourism is one of the leading growing segments of the tourism industry. Many tourists who visit heritage sites seek a value-added and authentic experience, when compared with the traditional products or mass destinations. Considering the importance of tourist`s satisfaction in what regards the revisit intentions and word-ofmouth referrals, which in turn influence the economic development of the tourist destination, this study attempts to investigate the relationship between cultural/heritage destination attributes and tourist`s satisfaction. The study area for this paper is the city of Guimarães, in the northwest of Portugal. This city is a place of strong symbolic and cultural significance and was deemed a world heritage site (UNESCO) in the year 2001. In 2012, Guimarães was one of the cities that hosted the European Capital of Culture (ECOC). All this enhanced its tourism potential and increased the amounts of visitors. The methodology consists of quantitative research based on a self-administered survey applied to tourists who visited Guimarães in the first half of 2015. Based upon the empirical results of this study, several recommendations can be made to increase tourists’ satisfaction vis-à-vis to Guimarães, regarding tourists’ needs, attributes valorization and cultural/heritage sustainability.